Influence of cation substitution on optical constants of (Cu₁₋ₓAgₓ)₇SiS₅I mixed crystals - Studenyak, I.P.; Bereznyuk, S.M.; Pop, M.M.; Studenyak, V.I.; Pogodin, A.I.; Kokhan, O.P.; Grančič, B.; Kúš, P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2020)
(Cu₁₋ₓAgₓ)₇SiS₅I mixed crystals were grown using the vertical zone crystallization method; they have been shown to crystallize in a cubic structure ( 4⎺3). The diffuse reflection spectra for the powders of (Cu₁₋ₓAgₓ)₇SiS₅I mixed crystals were measured at room temperature. Refractive indices and extinction coefficients for (Cu₁₋ₓAgₓ)₇SiS₅I mixed crystals were obtained from spectral ellipsometry measurements. A nonlinear decrease of the energy pseudogap and a nonlinear behavior with the maximum of refractive index have been revealed with increasing the Ag content. The dispersion of refractive indices of (Cu₁₋ₓAgₓ)₇SiS₅I has been described in the framework of different models.